Bandgap energy and dielectric function of GaOBr monolayer using density functional theory and beyond. (April 2021) - Barhoumi, M.; Sfina, N.; Said, M.
Abstract: In the last years, 2D materials beyond graphene have a great interest in the field of nanoelectronics and nano-optics applications. Based on the density theory and beyond (i.e., GW, RPA, and BSE), we study the vibrational, electronic, and optical properties of a new 2D GaOBr monolayer. In this framework, we have found that this 2D sheet is dynamically stable, which determined by their phonon dispersion. Our GW results show that the bandgap energy value of this sheet is ~ 5.20 eV, which is larger than the bandgaps of the REOBr monolayers (RE = Tb, Dy, Ho, Er, and Tm). Surprisingly, for the valence band, we have obtained two maxima, one is located at Γ point and the other appears at the X-point. The influence of an electric field on the electronic band structures of the GaOBr monolayer is also studied. In this framework, we obtained the application of the electric field significant changes in the position of VBM and CBM. Furthermore, we found that the BSE approach is the best technique to represent the dielectric function of GaOBr. Graphical abstract: Image 1 Highlights: We study the electronic and optical properties of GaOBr monolayer. The GaOBr monolayer is dynamically stable, which determined by their phonon dispersion. Our GW results show that the bandgap energy of GaOBr is significantly larger than the bandgaps of REOBr. The BSE approach is the best technique to represent the dielectric function of GaOBr.